2021
DOI: 10.3390/toxins13110788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis ZJ-2019-1 on Zearalenone Toxicosis in Female Gilts

Abstract: The purpose of this research was to investigate the toxicity of zearalenone (ZEN) on the growth performance, genital organs, serum hormones, biomarkers, and histopathological changes of female gilts and to evaluate the efficacy of Bacillus subtilis ZJ-2019-1 in alleviating ZEN toxicosis in gilts. Twenty-four female gilts were randomly allocated to four groups with six replicates per group and one gilt per replicate, fed on four feeds prepared previously, which were basic diet (control group, C group), ZEN diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The levels of ZEN metabolites (α-ZEL and β-ZEL; see Table 2 and Table 3 , Figure 1 ) in intestinal tissues were proportional to the administered doses and time of exposure. The proportions of α-ZEL and β-ZEL were similar to those noted in other studies [ 3 ], which is natural in our opinion [ 5 , 45 ]. The bioavailability of ZEN metabolites in intestinal tissues was influenced by biotransformation processes during pubescence.…”
Section: Discussionsupporting
confidence: 91%
“…The levels of ZEN metabolites (α-ZEL and β-ZEL; see Table 2 and Table 3 , Figure 1 ) in intestinal tissues were proportional to the administered doses and time of exposure. The proportions of α-ZEL and β-ZEL were similar to those noted in other studies [ 3 ], which is natural in our opinion [ 5 , 45 ]. The bioavailability of ZEN metabolites in intestinal tissues was influenced by biotransformation processes during pubescence.…”
Section: Discussionsupporting
confidence: 91%
“…Chang et al [ 42 ] reported that Bacillus subtilis could be used as the main component of compound probiotics; if these are added to feed, they could increase the production performance and alleviate the hepatic tissue damage of broilers by aflatoxins B1 and ZEN. Zhang et al [ 43 ] proved that Bacillus subtilis , if added to feed, could ease the toxicity of female pigs and alleviate cell damage. Shen et al [ 44 ] demonstrated that biodegradable Bacillus subtilis, as an additive, could significantly lower the concentrations of immunoglobulin G (IgG), immunoglobulin M (IgM), interleukin-2 (IL-2) and tumor necrosis factor-α (TNF-α) of gilts which are fed a ZEN-contaminated diet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has indicated that vulva swelling is the main clinical symptom of ZEN-induced toxicity in mammals [23,24], which has an adverse impact on the reproductive system and the breeding performance. Similarly, our data also indicated that ZEN significantly caused an increase in vulva size.…”
Section: Discussionmentioning
confidence: 99%